Revitalizing Mangroves for Inclusive Ecotourism: A Participatory Model from Muara Gembong, Indonesia - Manik, Amira Alrizky; Putri, Anggi Ananta; Pratiwi, Ni Komang Indah; Helmayanti, Sefhia; Koso, Wa Ode Nesha Rahmadinah; Rahmiati, Filda (Journal of Rural and Regional Innovation Studies, 2025)
The destruction of the mangrove ecosystem in the coastal area of Muara Gembong, Bekasi Regency, has led to a decline in environmental quality and reduced economic potential for the local community. Mangrove rejuvenation is a strategic solution to support sustainable ecotourism development while improving community welfare. The purpose of this study is to offer more information regarding the use of mangrove revitalisation as a strategy for developing sustainable ecotourism in Muara Gembong. The method used is a Community-Based Participatory Research (CBPR) approach with participatory observation techniques and documentation studies. The data were analysed descriptively by following the stages of data reduction and drawing conclusions. The results of this study indicate that mangrove regeneration in Muara Gembong has great potential as a new opportunity to develop sustainable ecotourism. It is impact on ecological and economic outcomes able to improve the welfare of coastal communities while preserving the environment. In conclusion, mangrove revitalisation in Muara Gembong is an effective model for developing sustainable ecotourism that has a positive impact on the environment and local economy enhances overarching policies for sustainable tourism management. Moreover, the possibility for replication of community-based strategy that fosters socioeconomic empowerment across Indonesia’s coastal areas.